Regenerative approach in the treatment of grade II furcations: a case report - Hasanuddin Thahir; Dian Setiawati (Journal of Dentomaxillofacial Science, 2019)
Objective: A grade II furcation involvement has been defined as a defect having a horizontal loss attachment of 3 mm or greater but not through the entire furcation. There are several techniques used alone or in combination considered to achieve periodontal regeneration. This case report aims to describe regenerative approach in the treatment of grade II furcation defects in maxillary molars. Method: A-43-years old male reported to the Department of Periodontics with a complaint of pain. At the initial visit, scaling and root planning was done. It was followed by periodontal regenerative therapy using bone graft and resorbable membranes.Results: The treatment for overall seemed success with healthy periodontium and complete closed defect with bone fill, based on the clinical and radiographic development of Â the patient at the end of six month follow up.Conclusion: The regenerative approach such as resorbable GTR membrane with bone material was more effective than open debridement alone, in the treatment of furcation defects.